2010
DOI: 10.1371/journal.pone.0011220
|View full text |Cite|
|
Sign up to set email alerts
|

Functional and Molecular Effects of Arginine Butyrate and Prednisone on Muscle and Heart in the mdx Mouse Model of Duchenne Muscular Dystrophy

Abstract: BackgroundThe number of promising therapeutic interventions for Duchenne Muscular Dystrophy (DMD) is increasing rapidly. One of the proposed strategies is to use drugs that are known to act by multiple different mechanisms including inducing of homologous fetal form of adult genes, for example utrophin in place of dystrophin.Methodology/Principal FindingsIn this study, we have treated mdx mice with arginine butyrate, prednisone, or a combination of arginine butyrate and prednisone for 6 months, beginning at 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 27 publications
5
40
1
Order By: Relevance
“…An 8-week study of prednisolone in mdx mice improved specific force and decreased the number of centrally nucleated myofibers (9). However, 3 months of daily prednisone in mdx mice resulted in weight loss, reduced strength, and increased fibrosis in the heart, suggesting that longer, chronic administration may be problematic (10). Recently, it has been shown that GC steroids rely on Krüppel-like factor 15 (Klf15), a Krüppel like transcription factor, to mediate ergogenic muscle performance effects (11).…”
Section: Introductionmentioning
confidence: 99%
“…An 8-week study of prednisolone in mdx mice improved specific force and decreased the number of centrally nucleated myofibers (9). However, 3 months of daily prednisone in mdx mice resulted in weight loss, reduced strength, and increased fibrosis in the heart, suggesting that longer, chronic administration may be problematic (10). Recently, it has been shown that GC steroids rely on Krüppel-like factor 15 (Klf15), a Krüppel like transcription factor, to mediate ergogenic muscle performance effects (11).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 MRI, in particular T2-weighted MRI, is sensitive to alterations in muscle chemistry and structure induced by processes like damage/inflammation and fat infiltration, [10][11][12][13][14][15][16][17] and therefore may have the potential to detect the effects of corticosteroid treatment on dystrophic muscles. Magnetic resonance spectroscopy (MRS) allows quantification of chemical compounds and can separate lipid and water components, allowing a more targeted investigation of skeletal muscles in DMD.…”
mentioning
confidence: 99%
“…These can in part be attributed to reduced ROS-mediated activation of NF-B and its downstream targets, MMP-2 and -9 [133] (see section 3.3.1) Similar beneficial effects were observed using molsidomine (Corvasal ® ), the established drug for the treatment of coronary disease and pulmonary fibrosis which is metabolised into a NO donor in the liver [131]. However there have been subsequent reports that long term arginine supplementation reduces/abolishes these beneficial effects [134] and actually promotes fibrosis [135]. Furthermore, no improvement in cardiac disease has been observed following treatment designed to enhance arginine metabolism [134,136].…”
Section: Utrophin Upregulationmentioning
confidence: 78%
“…However there have been subsequent reports that long term arginine supplementation reduces/abolishes these beneficial effects [134] and actually promotes fibrosis [135]. Furthermore, no improvement in cardiac disease has been observed following treatment designed to enhance arginine metabolism [134,136]. It is therefore unlikely that pharmacological activators of the NO pathway constitute a realistic treatment for DMD.…”
Section: Utrophin Upregulationmentioning
confidence: 99%